Calcium Ion-Dependent Monoclonal Antibody Against Human Fibrinogen: Preparation, Characterization, and Application to Fibrinogen Purification - Takebe, Mikihiro; Soe, Gilbu; Kohno, Isao; Sugo, Teruko; Matsuda, Michio (Thrombosis and Haemostasis, 1995)
We have produced a high-affinity monoclonal antibody classified as IgG1 with K-type light chains that recognizes the calcium ion(Ca2+)- dependent conformation of the D-domain of human fibrinogen. Binding of fibrinogen in solution to the insolubilized antibody increased in the presence of increasing concentrations of up to 2 mM Ca2+, the half-maximal binding being reached at 130 μM Ca2+. The dissociation constant was estimated to be 1.6 × 10-8 M at 2 mM Ca2+. The antibody was found also to be dependent on other divalent metal ions including Zn2+, Mn2+, Co2+ and Cu2+, but not Ba2+, Mg2+ or Sr2+. The synthetic Gly-Pro-Arg-Pro-amide peptide, which has recently been shown to bind to close proximity to the calcium binding site in the D-domain, was unable to elicit the conformation for the antigen to be recognized by this antibody. This antibody was found to be a suitable ligand for the immunoaffinity chromatography of normal and abnormal fibrinogens directly from citrated plasma depleted of the vitamin K-dependent proteins or heparinized plasma by eliminating the precipitation procedure widely adopted in conventional techniques of fibrinogen purification. Indeed, fibrinogen Marburg I with the Aa chains depleted of the carboxy-terminal Aα(461-610) residue segment has been purified by this technique, although this dysfibrinogen was difficult to purify by conventional precipitation techniques.